The fast forward MBA in project management - Verzuh, Eric.; ebrary, Inc. (Hoboken, N.J. : Wiley, 2011)
"An updated and revised edition of the bestselling guide to managing projectsFor any professional responsible for coordinating projects among different departments, across executive levels, or with technical complexity, The Fast Forward MBA in Project Management offers comprehensive instruction on how to deliver on time and on budget. Get the step-by-step advice you need to find the right sponsor, clarify objectives, and set realistic schedules and budget projections. This Fourth Edition of the 200,000-copy bestseller now covers critical new topics including: software and IT projects, agile techniques, and project selection.Perfect for beginners or experienced managers needing to bring their systems up to date, The Fast Forward MBA in Project Management allows readers to extract maximum information in minimum time. The most comprehensive introduction to project management, updated to reflect changes in the business environment over the past few years Full of downloadable forms and spreadsheets to help you implement the techniques in the book Offers updated advice on getting the most from Microsoft Project "--
Includes index.
Electronic reproduction.
Keywords: Project management; Electronic books